An experimental study on dielectric response of the crosslinked polyolefin (XLPO) insulation of the unshielded cable under electric field and heat flux - Singhasivanon, Jakawan; Jirasuwankul, Nirudh (My University, 2021)
Nowadays, crosslinked polyolefin cables (XLPO cables) are more popular and more famous for electrical insulation. In order to study and analyze the characteristics of insulation. The polarization and depolarization of current measurements (PDC measurement) is one of the advance methods that can compute and provide dielectric reaction parameters. In this paper, aim to study dielectric response of the XLPO insulation of unshielded cables under electric fields and heat fluctuations by measuring permittivity (ϵ′, r), conductivity (σ) and dissipation factors (Tan δ). The experimental results indicate permittivity is rather constant at different field strengths and temperatures and are similarly to XLPE insulation. It is also found that the activation energy of XLPO insulation is 0.77 eV. Future more, action energy in this research can excite electrons or ions in valent band within insulations to change the state from non-conductivity to conductivity.
Keywords: Activation energy; Conductivity; Crosslinked polyolefin; Dissipation factor; Permittivity